2019
DOI: 10.1002/acp.3503
|View full text |Cite
|
Sign up to set email alerts
|

Taking a new look at seductive details

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As evidenced by the current study, and by the recent special issue of Applied Cognitive Psychology (Eitel & Kühl, 2019a ), many studies have found null or beneficial effects of seductive details. Although Mayer still asserts that “adding interesting but irrelevant material to a lesson hurts learning” (Mayer, 2019 , p. 141), we hold that this admonition needs to be qualified. The current study, recent publications in the special issue, and the meta‐analyses all highlight the fact that the seductive detail effect is mediated by a variety of factors.…”
Section: Discussionmentioning
confidence: 77%
“…As evidenced by the current study, and by the recent special issue of Applied Cognitive Psychology (Eitel & Kühl, 2019a ), many studies have found null or beneficial effects of seductive details. Although Mayer still asserts that “adding interesting but irrelevant material to a lesson hurts learning” (Mayer, 2019 , p. 141), we hold that this admonition needs to be qualified. The current study, recent publications in the special issue, and the meta‐analyses all highlight the fact that the seductive detail effect is mediated by a variety of factors.…”
Section: Discussionmentioning
confidence: 77%
“…Being entertaining does not always interfere with learning, but it can. For example, adding interesting but irrelevant tidbits of information to a text or lecture can decrease learning (Fries, DeCaro, & Ramirez, 2019; Harp & Maslich, 2005; Mayer, Griffith, Jurkowitz, & Rothman, 2008; Mayer, 2019). The bottom line is, SET can cause professors to give students what they want rather than what they need.…”
Section: Three Shortcomings Of Setmentioning
confidence: 99%
“…The seductive details effect is one of the most popular research topics in multimedia learning (Li et al, 2019) and research has shown that seductive details can inhibit learning, but this is not always the case as a number of variables may moderate the effect (Mayer, 2019). It remains unclear whether ego depletion is one of the potential moderators.…”
Section: Introductionmentioning
confidence: 99%